Experimental investigation and optimization analysis on thermoelectric water generator integrated with heat pipe. (25th January 2023) - Zhang, Zijun; Qin, Yang; Fan, Hui; Jin, Sumin; Su, Lei; Xu, Jiu; Zhu, Lin
Highlights: Thermoelectric water generator integrated with heat pipe (HPTEWG) is proposed. HPTEWG and thermoelectric water generator (TEWG) are compared experimentally. HPTEWG can achieve higher cooling capacity than TEWG by 34.11 W. Maximum water generation increment in HPTEWG by 38.95 ml/h can be achieved. Structure configurations of HPTEWG are optimized to gain maximum water generation. Abstract: As scare freshwater resources have been severely stressed by climate change, population growth and water pollution, demands of efficient water generation methods and devices urgently increase. To further improve the water generation capacity of thermoelectric water generator (TEWG), a novel TEWG integrated with heat pipe (HPTEWG) is proposed and studied by using experimental and simulation methods. Rather than the heat sink of the TEWG, the heat pipe is utilized to precool moisture air before the thermoelectric cooler to achieve the goal. Experimental results show that the maximum improvement in cooling capacity and water generation of HPTEWG can be 34.11 W and 38.95 ml/h when compared with TEWG under given operating condition. Besides, the effects of the input power of TEWG, inlet air temperature, relative humidity and mass flow rate on the performances of two system are experimentally investigated as well. In addition, a validated theoretical optimization model is built to optimize the structure configuration of the HPTEWG. The maximum water generation of the HPTEWG can be achieved when optimal area allocation ratio of HP and TEWG are chosen under constant total area condition. It is hope that the results can provide theoretical basis for the thermoelectric water generator development and application.